Faktor - Faktor yang Mempengaruhi Minat Belajar Peserta Didik - Rina Dwi Muliani Rina Dwi Muliani; Arusman Arusman (Jurnal Riset dan Pengabdian Masyarakat, 2022)
Learning is a process that involves various things that are owned by each individual. Learning is not only about lessons but skills, skills, interests, perceptions and habits that are often carried out by interest in the learning process is an aspect in psychology that affects every individual in learning. Because the interests that someone has will cause a sense of love and a sense of attachment to a thing or activity without any compulsion. This research was conducted with the aim of knowing the factors that influence students' interest in learning. This research was conducted using a qualitative descriptive research method. The population and samples used are students. Based on the overall results of the data obtained, it can be seen that the factors that influence students' interest in learning consist of internal and external factors.